Ethiopia : Public Expenditure Review, Volume 1. Main Report - World Bank (Washington, DC, 2013)
This Public Expenditure Review (PER), is the seventh in a series of annual PERs for Ethiopia, addressing issues of public expenditure management, relevant to the government, and donors. As such, and as a result of a shared understanding between the Government, and a core donor group, the report shifts the emphasis from analysis, to problem solving, and, from perspective of the federal government, to the joint perspective of the federal, and regional governments. The progressive fiscal toll resulting from the border conflict, is examined within an economic context, for although the government did contain the fiscal impact of the conflict by financing defense expenditures through budget contingencies, and other budgetary funds, it appears fiscal limits have been reached, as the significant recourse to domestic financing, and reduced capital spending, jeopardize the expansion of basic social services. Fiscal performance is reviewed, fiscal outcomes are projected, and risks and alternatives analyzed, within the context of an information systems for strategic expenditure management, through performance indicators for budget planning, and financial reporting. However, the report identifies the need to provide technical assistance for developing output, and outcome indicators, for building databases, and for capacity building, which would clarify acceptance by the government, of PER recommendations, and its implementation. It is suggested that a Joint Review Mission, based on the Annual Review Meeting, be adapted for the PER process, to include an institutional involvement of the regions, in identifying, analyzing, and implementing recommendations.